Morphometrics Of Gastropods In The Waters Of The Babura River, Medan City - Masdiana Sinambela; Andreas Simorangkir; Arman Harahap (International Journal of Science and Environment (IJSE), 2025)
Gastropod morphometrics in the waters of the Babura River, Medan City, is the title of research carried out to find out how Gastropod morphometrics are useful for knowing growth patterns, eating habits, and also the influence of physical and chemical parameters. So far there has been no research on morphometric measurements of gastropods in the Babura River. Data collection for this research will begin from July 2023 to October 2023. There are three research stations, namely: station 1 on Jalan Bunga Rampai IV Simalingkar B, station 2 on Jalan Karyawisata tip Namurambe, and station 3 in Taman Beringin Medan city with as many repetitions as possible. 3 repetitions, so that the data obtained is more accurate. Gastropods in the Babura river have been identified. Shell morphometric measurements include shell length (A), shell width (B), aperture length (C), number of threads (D). This type of research is ex post de facto. The morphometrics of gastropods found were six species, namely: Filopaludina javanica had an average (mm) for A 18.5, B 13.9, C 3.5; Melanoides tuberculate has a mean for A 21.53, B 8.39, C 6.43, Terebia granifera has a mean for A 18.05, B 7.75, C 4.30, Thiara scraba has a mean for A 19.50, B 15.05, C 16.90, with each number of threads (D) being 4, Lymneae rubiginosa A 6.75, B 2.75, C 3.55, and Dnya 2, Pomaceae canaliculate A 17.00, B 10.85, C 11.48, and D 3. The frequency of presence of each species is Filopaludina javanica 33.33%; Melanoides tuberculate 100%, Terebia granifera has an average of 66.66%, Thiara scraba 66.66%, Lymneae rubiginosa 33.33%, Pomaceae canaliculate 66.66% The results of measuring physical/chemical parameters are generally still below the threshold except for BOD, COD , and ammonia which should be zero. The heavy metals copper (Cu), lead (Pb) and cadmium (Cd) are still far below the threshold.